Avaliação da atividade antibacteriana e identificação de compostos fenólicos do mel de abelhas sem ferrão (Hymenoptera, Apidae, Meliponinae) Melipona compressipes manaosenses e Melipona seminigra - Pimentel, Renah Boanerges de Queiroz (2010)
ABSTRACT- The honey of bees has been used from the antiquity in the most varied application forms in the medicine, which is due mainly their proven therapeutic properties. Nowadays it seems to be seen as an alternative to the use of the antibiotics that causing concern front to the emergence of resistant bacteria due to the indiscriminate use. Before that, this work had as objective evaluates the antibacterial potential of the honey of two species of indigenous bees without sting and some honeys commercial front to six patogenic bacteria to the man, and to identify their fenolics compositions. For the antimicrobial tests two techniques were used, the one of the diffusion in agar and the one of dilution in tube. Two honeys stood out how being the one of larger activity using the diffusion method in agar, the honey 1C-2 (Melipona compressipes manaosensis) inhibiting the growth of the microorganisms: Staphylococcus aureus, Escherichia coli (0157:H7), Proteus vulgaris, Shigella sonnei e Klebsiella sp., and the honey IE (honey of Apis mellifera, adorned of eucalyptus) inhibiting the growth of the microorganisms: Escherichia coli (0157:H7), Proteus vulgaris, Shigella sonnei, Salmonella paratyphi, Klebsiella sp. Using the dilution technique, all the seven samples demonstrated good activity, inhibiting the growth of all of the bacteria in the but varied dilutions, indicating the largest sensibility of that technique. Several picks were revealed in High Performance Liquid Chromatography, that can correspond to fenolics compositions. Only the flavonoid rutin, was identified in the sample 1C-2. The information contained in this work of identification of compositions fenolics and antimicrobial in vitro tests, they can offer to the honey advantages in the control of the bacterial growth and in the treatment of certain problems of health. Key words: Antibacterial honey, Bees without sting, Flavonoids, HPLC